Study on the value of gastrin 17 and aldehyde dehydrogenase 1 in gastric juice for early diagnosis in gastric cancer - Wang, Yanfang; Liu, Hui; Li, Xiang; Jin, Juan; Yan, Bo (Frontiers in Oncology, 2025)
ObjectiveTo investigate the diagnostic utility of aldehyde dehydrogenase 1 (ALDH1) and gastrin 17 (G-17) levels in the gastric juice of patients with gastric cancer and to track changes in the levels of these markers in the gastric juice of these patients.Methods126 individuals were diagnosed via gastroscopy. This trial includes gastric mucosal histology and gastroscopy performed at Hefei Second People’s Hospital between March 2023 and March 2024. On the basis of the results of gastroscopy and gastric mucosal histology, all the participants were categorized into three groups: 30 patients with gastric cancer (GC), 34 patients with gastric ulcer (GU) and 62 patients with gastritis. Thirty patients with chronic nonatrophic gastritis were chosen from the physical examination center, and thirty-two patients with chronic atrophic gastritis (CAG) composed the gastritis group. As the control group, they were chosen at the physical testing center. An enzyme-related immunosorbent assay (ELISA) was used to quantify the levels of G-17 and ALDH1 in each group. A correlation study was performed on the levels of ALDH1 and G-17 in the gastric juice. By using binomial logistic regression analysis, the impact of G-17 and ALDH1 in gastric juice on the incidence of gastric cancer was examined. To illustrate the predictive usefulness of G-17 and ALDH1 in gastric juice for GC diagnosis, a receiver operating characteristic (ROC) curve was generated.ResultsThe gastric juice of the gastric cancer group had higher levels of ALDH1 and G-17 than did the gastric juice of the gastritis group and GU group (P < 0.05). The levels of ALDH1 and G-17 in gastric juice of gastric ulcer group were higher than those of atrophic gastritis group and control group (P < 0.05). The levels of ALDH1 and G-17 in gastric juice of atrophic gastritis group were statistically significant compared with those of control group (P < 0.05). The development of gastric cancer was significantly influenced by elevated levels of ALDH1 and G-17 in gastric juice (OR= 1.095, 1.018; both P <0.05); the AUCs for the combined diagnosis of gastric cancer and elevated levels of G-17 and ALDH1 in gastric juice were 0.792, 0.757, and 0.695, respectively.ConclusionThe development of gastric cancer is influenced by increased levels of ALDH1 and G-17 in gastric juice. The diagnosis of gastric cancer may be made more accurately by combining the two gastric fluid markers, which can be found in gastric juice.